Simulation of Pollutant Dispersion in the Atmosphere under Unstable Conditions Using an Analytical Solution - Quadros, Regis S. de; Gonçalves, Glênio A.; Buske, Daniela; Contreira, Juliana; Cezimbra, Renata A. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2013: Anais do IV Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2013)
Analytical solutions of equations are of fundamental importance in understanding and describing physical phenomena. In this work we present the solution of the two-dimensional advection-diffusion equation in Cartesian geometry by the GILTT approach, considering that the eddy diffusivity and the vertical wind profile depends on the z variable. To carry more information of the original problem, a Sturm-Liouville problem given by Bessel functions is used as basis in the solution. Numerical simulations and comparisons with experimental data are presented.